Two cases of failed back surgery syndrome after correction and stabilization surgery for scoliosis with Harrington instrumentation - Marino, Marco Andrea; Scaglia, Marco; Pasquetto, Davide; Sambugaro, Elena; Tromponi, Chiara; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2016)
We report two cases of adjacent segment degeneration in patients with idiopathic scoliosis who underwent surgical treatment with Harrington instrumentation in young age. Both patients developed a symptomatic degeneration of the disk immediately under the last stabilized level and were treated with decompression and stabilization. Clinical and radiological results are satisfactory at the follow-up.